Kawasan Strategis Pariwisata Nasional (KSPN) Borobudur Dalam Perspektif Poltik Hukum Otonomi Daerah - Triantono, Triantono; Marizal, Muhammad; Ardhi Razaq A, Muhammad (Jurnal Hukum & Pembangunan, 2023)
Policy of the Borobudur National Tourism Strategic Area (KSPN) still has problems in terms of central and regional legal policy relations, village authority, and the approach of community participation. Research related to this was carried out using a normative juridical method with an empirical approach. Data was collected through the collection of legal materials, observations, in-depth interviews, and FGDs with key groups. The collected data is then processed and analyzed to produce an analytical description. The results of the study show that the policy of the Borobudur area as a strategic national tourism area (KSPN) opens opportunities, especially in improving regional management to improve community welfare. However, problems in the era of regional autonomy and the increasing capacity of village government authorities are still encountered regarding the synergies of the legal policy of managing the Borobudur area as an area of cultural heritage, tourism and education. The problem of participation, protection and empowerment of communities around the Borobudur area is also still encountered and becomes an important point through a protective-responsive empowerment approach.